ANALISIS KANDUNGAN TIMBAL (Pb) DALAM DAUN TANAMAN DI RUANG TERBUKA HIJAU - Nurmawan, W.; Ogie, Tommy B.; Kainde, R. P. (EUGENIA, 2019)
Lead (Pb) is a highly toxic heavy metal that can have a negative influence on chlorophyll because most of it is accumulated by plant organs, namely leaves, stems, and roots, as well as soil around plants. This study aims to examine the Pb content in the leaves of Angsana (P1), Trembesi (P2), and Mahoni plants in the urban green spaces around UNSRAT (T1), KONI (T2) and Sparta Tikala Sport Field (T3) in Manado. Pb content testing uses the AAS (Atomic Absorption Spectrophotometery) method in the laboratory of Manado Industrial Standards Agency. This research was compiled using a Randomized Block Design (RCBD) with 2 treatment factors, namely tree species (P) and sampling locations (T). Each treatment was repeated 3 times to obtain 27 experimental units. The results showed that the treatment of tree species and sampling locations had a significant influence on lead sorption by leaves. Interaction of P3T3 treatment produced the highest lead sorption at 1.14 ppm, which was not significantly different from P3T1 (1.12 ppm), P3T2 (1.07 ppm), P2T2 (1.01 ppm), P2T3 (0.97 ppm), P2T1 (0.97 ppm), P1T3 (0.92 ppm) but significantly different from P1T2 (0.89 ppm) and P1T1 (0.87 ppm).Â  Overall, the results of Pb sorption are within the normal limits of Pb content in plants ranging from 0.5 to 3.0 ppm.